Pengaruh Keterampilan Guru Kelas Terhadap Efektifitas Belajar Siswa Kelas 2 SDN Jatisura 1 Kecamatan Cikedung Kabupaten Indramayu - Tatik Tatik; Sumarta Sumarta (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study aims to analyze the impact of classroom teacher skills on the learning effectiveness of second-grade students at SDN Jatisura 1, Cikedung District, Indramayu Regency. The research method employed is a survey involving 30 students and one classroom teacher. The results indicate that the teacher's skills in teaching, including classroom management, media utilization, and varied teaching techniques, positively contribute to student learning outcomes. Students who rated their teacher's skills positively tend to have better learning outcomes compared to those who rated their teacher's skills as average or poor. These findings emphasize the importance of enhancing teacher skills to improve learning effectiveness at the elementary education level. Therefore, teacher training programs should focus on relevant skill enhancement.